2019
DOI: 10.3389/fnins.2019.01145
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile Stimulation Based on the Fundamental Frequency Can Improve Melodic Contour Identification of Normal-Hearing Listeners With a 4-Channel Cochlear Implant Simulation

Abstract: Cochlear implant (CI) users’ poor speech recognition in noise and music perception may be both due to their limited access to pitch cues such as the fundamental frequency (F0). Recent studies showed that similar to residual low-frequency acoustic hearing, vibrotactile presentation of the F0 significantly improved speech recognition in noise of CI users. The present study tested whether F0-based vibrotactile stimulation can improve melodic contour identification (MCI) of normal-hearing listeners with acoustical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Another recent set of studies have shown evidence that haptic stimulation might enhance music perception in CI users. Haptic stimulation on the fingertip ( Huang et al, 2019 ) or wrist ( Luo and Hayes, 2019 ) was found to improve melody recognition. In both these studies, haptic stimulation was delivered via a single motor.…”
Section: Electro-haptic Stimulationmentioning
confidence: 99%
“…Another recent set of studies have shown evidence that haptic stimulation might enhance music perception in CI users. Haptic stimulation on the fingertip ( Huang et al, 2019 ) or wrist ( Luo and Hayes, 2019 ) was found to improve melody recognition. In both these studies, haptic stimulation was delivered via a single motor.…”
Section: Electro-haptic Stimulationmentioning
confidence: 99%
“…However, this and other pitch extraction approaches for enhancing music perception using haptics (e.g., Luo and Hayes, 2019), are not designed to accommodate musical pieces with multiple simultaneous harmonic sounds. More advanced multipitch extraction methods will likely be required if they are to be effective across a range of musical pieces.…”
Section: Source Separationmentioning
confidence: 99%
“…Two further studies reported behavioral results for wearable devices. One wrist-worn device extracted the fundamental frequency, like the mosaicOne_B, but mapped it to changes in the frequency and amplitude of the haptic signal (which varied together), rather than spatial location ( Luo and Hayes, 2019 ). Critically, unlike for the mosaicOne_B, this meant that intensity information could not be delivered.…”
Section: Current Systems For Improving Music Perception Using Haptic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in addition to substituting auditory input for haptic input, it has been shown that it is possible to augment auditory input with haptic input; three recent studies have shown that CI users' ability to recognise speech in background noise was enhanced when speech information was presented through haptic stimulation on the wrists 22,29 or fingertips 30 . Two other recent studies have shown that haptic stimulation can improve melody identification in CI users, using a single-channel haptic stimulation device strapped to the wrist 31 or fingertip 32 . In the current study, we evaluated the ability of our new mosaicOne_B device, which delivers pitch information through multi-channel haptic stimulation along the forearm, to provide accurate pitch information.…”
mentioning
confidence: 99%